Tradição Camponesa e Modernização:experiências dos colonos do perímetro irrigado de Morada Nova - CE - Braga, Ana Maria de Fátima Afonso (2003)
The research work deals with the experiences and memory of the settlers of the irrigated perimeter of Morada Nova. Initially the sertanejo is seen in the institutional environment thought by the state, in the sense of developing irrigated agriculture [...]